2010
DOI: 10.1371/journal.pone.0012500
|View full text |Cite
|
Sign up to set email alerts
|

Gene Knock-Outs of Inositol 1,4,5-Trisphosphate Receptors Types 1 and 2 Result in Perturbation of Cardiogenesis

Abstract: BackgroundInositol 1,4,5-trisphosphate receptors (IP3R1, 2, and 3) are intracellular Ca2+ release channels that regulate various vital processes. Although the ryanodine receptor type 2, another type of intracellular Ca2+ release channel, has been shown to play a role in embryonic cardiomyocytes, the functions of the IP3Rs in cardiogenesis remain unclear.Methodology/Principal FindingsWe found that IP3R1−/−-IP3R2−/− double-mutant mice died in utero with developmental defects of the ventricular myocardium and atr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 36 publications
5
53
0
Order By: Relevance
“…Calcineurin-dependent translocation of NFATc1 into the nuclei, a good marker for proper calcium homeostasis in AVC endocardial cells (de la Pompa et al, 1998;Ranger et al, 1998;Crabtree and Olson, 2002), was not observed in Tmem100 null embryos. Suppression of NFATc1 translocation in AVC endocardial cells was also reported in mouse embryos harboring the Itpr1/Itpr2 deletion, in which calcium homeostasis was dysregulated by the lack of inositol 1,4,5-triphosphate receptor 1 and 2 (Uchida et al, 2010). Since the treatment of Tmem100 null heart with the calcium ionophore was sufficient to induce nuclear translocation of NFATc1, upstream calcium signaling, but not the responsiveness of calcineurin or NFATc1, is likely to be impaired in Tmem100 null embryos.…”
Section: Developmental Dynamicsmentioning
confidence: 68%
See 2 more Smart Citations
“…Calcineurin-dependent translocation of NFATc1 into the nuclei, a good marker for proper calcium homeostasis in AVC endocardial cells (de la Pompa et al, 1998;Ranger et al, 1998;Crabtree and Olson, 2002), was not observed in Tmem100 null embryos. Suppression of NFATc1 translocation in AVC endocardial cells was also reported in mouse embryos harboring the Itpr1/Itpr2 deletion, in which calcium homeostasis was dysregulated by the lack of inositol 1,4,5-triphosphate receptor 1 and 2 (Uchida et al, 2010). Since the treatment of Tmem100 null heart with the calcium ionophore was sufficient to induce nuclear translocation of NFATc1, upstream calcium signaling, but not the responsiveness of calcineurin or NFATc1, is likely to be impaired in Tmem100 null embryos.…”
Section: Developmental Dynamicsmentioning
confidence: 68%
“…The CnA molecule with the deletion of calmodulin binding and autoinhibitory domains is constitutively active independently of cellular calcium concentration. Expression of constitutively-active CnA, but not that of wild-type CnA, restored EndMT impaired in the AVC explants from the embryos null for the genes encoding inositol 1,4,5-trisphosphate receptors, Itpr1 and Itpr2 (Uchida et al, 2010). By examining the effects of constitutively-active and wild-type CnA expression, we can test if calcium-dependent calcineurin signaling is dysregulated in the AVC explants from Tmem100 null embryos.…”
Section: Restoration Of Endmt In Tmem100 Null Avc Explants By Constitmentioning
confidence: 99%
See 1 more Smart Citation
“…These isoforms differ in their binding affinities for IP 3 , with IP 3 R2 being the most and IP 3 R3 being the least sensitive to the ligand (Iwai et al, 2007;Tu et al, 2005). All three IP 3 Rs are expressed in human adult CMs, but their subcellular localizations have not been studied (Nakazawa et al, 2011;Uchida et al, 2010). In rat adult CMs, these are expressed at about 50-fold lower than those of RyRs; IP 3 R1s are localized around the nuclear envelope and SR, both of which are connected, while IP 3 R2s are dispersed throughout the cytosol in a punctate pattern (Bare et al, 2005;Li et al, 2005;Moschella and Marks, 1993).…”
Section: Regulation Of Intracellular Calcium Level By Ligand-operatedmentioning
confidence: 99%
“…requirement for phospholipase (PLC) δ1 and δ3 [4] that produce IP 3 for placentation led us to investigate the placental defects by deletion of any subtypes of IP 3 Rs. Our preliminary result revealed that embryonic vasculature in the labyrinth was impaired in the placenta double knockout for IP 3 R1 and IP 3 R3 at E9.25 ( Fig.…”
mentioning
confidence: 99%